2022-RA-989-ESGO Does fertility preservation affect the onset of the oncological treatment and the response to neoadjuvant chemotherapy in breast cancer?. (20th October 2022) - Baulies, Sonia; Devesa, Marta; Tresserra, Francesc; Izquierdo, Maxim; Fargas, Francesc; Rodríguez, Ignacio; Fàbregas, Rafael
Abstract : Introduction/Background: Study in breast cancer patients to assess whether fertility preservation (FP) can affect the onset of the oncological treatment and the pathological response in those patients who underwent neoadjuvant chemotherapy (NAC). Methodology: Patients with breast cancer who underwent fertility preservation and NAC are matched 1:2.45 to non-FP controls by age and date al diagnosis and are studied:. Timing between the diagnosis of breast cancer and the onset of oncological treatment was performed. Studying the pathological complete response (Miller Payne scale) among patients with FP compare to non-FP control group was also performed. Results: 20 patients with FP and NAC are studied between 2010–2019 and were compared to 49 non-FP patients. The median age at diagnosis was 36 years (28–39). The oncological characteristics are shown in table 1 .The time analysis in FP group was: 1.- Period of FP visit was 4 days (1–26), 2.- the period of FP (start of the stimulation treatment until the recovery of the oocytes) 12 days (7–20), 3.- the Period of onset of oncological treatment 7 days (1–27). The overall period took 26 days (18–51) compared to 17.5 days (1–60) in non-FP group (NS).Pathological complete response (Miller Payne 5): The pathological complete response was80% (16/20) in FP group versus 40.8% (20/49) in non-FP group. Analyzed by tumor subtype in FP group, a MP5 was achieved in 72.7% luminal tumor (8/11), 75% positive-HER2 (3/4), 100% triple negative (5/5) versus 19% luminal tumor (4/21), 41.6% (5/12) positive-HER2 and 68.7% triple negative (11/16) in non-FP group ( table 2 ) Conclusion: FP does not delay the onset of oncological treatment and our data do not suggest an adverse impact of FP on pathological complete response to NAC.